2020
DOI: 10.1111/aas.13684
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative MgSO4 infusion protects oxygenation and lung mechanics in COPD patients during general anesthesia. A randomized clinical trial

Abstract: Background: The purpose of this study was to examine the effects of an intraoperative MgSO 4 infusion on arterial oxygenation and lung mechanics in patients with moderate COPD undergoing cancer larynx surgery under general anesthesia (GA). Our primary outcome was arterial oxygenation determined by the PaO 2 and PaO 2 / FiO 2. The secondary outcomes were lung mechanics (peak airway pressure, airway plateau pressure, dead space, lung compliance, airway resistance) and postoperative complications. Methods: In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…These findings could help explain the positive effects of MgSO 4 infusions on dynamic compliance and dead space observed in this study. Our results are similar to those of a previous study conducted by Ahmed et al [ 20 ], which showed that an intraoperative infusion of MgSO 4 resulted in mild perioperative protective effects against both arterial oxygenation and lung mechanics in patients with moderate COPD following laryngectomy under general anesthesia.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These findings could help explain the positive effects of MgSO 4 infusions on dynamic compliance and dead space observed in this study. Our results are similar to those of a previous study conducted by Ahmed et al [ 20 ], which showed that an intraoperative infusion of MgSO 4 resulted in mild perioperative protective effects against both arterial oxygenation and lung mechanics in patients with moderate COPD following laryngectomy under general anesthesia.…”
Section: Discussionsupporting
confidence: 92%
“…Setting the power = 0.80 and α = 0.05 with using PASS 11 th release (Hintze, 2011) [24], a minimal sample size of 2 cases in each group was required to get statistically significant between assumed Δ PaO2/FiO2 (%) in MgSO4 and control groups -3.1 ± 0.2 and -12.2 ± 0.5 respectively (Ahmed et al, 2020) [20]. A sample size of 40 patients (20 in each group) was used to ensure that the sample was representative to our population.…”
Section: Sample Size Justificationmentioning
confidence: 99%
See 2 more Smart Citations